2018
DOI: 10.2147/hiv.s153185
|View full text |Cite
|
Sign up to set email alerts
|

Trends, treatment outcomes, and determinants for attrition among adult patients in care at a large tertiary HIV clinic in Nairobi, Kenya: a 2004–2015 retrospective cohort study

Abstract: BackgroundUnderstanding trends in patient profiles and identifying predictors for adverse outcomes are key to improving the effectiveness of HIV care and treatment programs. Previous work in Kenya has documented findings from a rural setting. This paper describes trends in demographic and clinical characteristics of antiretroviral therapy (ART) treatment cohorts at a large urban, referral HIV clinic and explores treatment outcomes and factors associated with attrition during 12 years of follow-up.MethodsThis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Known predictors of attrition include low initial CD4 T-cell lymphocyte counts, low baseline body mass index (BMI), history of hospitalization, advanced WHO clinical staging, older age at HIV diagnosis, and being a man 11 13 . Other studies from the region show anemia and decreased red blood cell counts and platelets as predictors of death during the first year of ART treatment 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Known predictors of attrition include low initial CD4 T-cell lymphocyte counts, low baseline body mass index (BMI), history of hospitalization, advanced WHO clinical staging, older age at HIV diagnosis, and being a man 11 13 . Other studies from the region show anemia and decreased red blood cell counts and platelets as predictors of death during the first year of ART treatment 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, finding was also higher when compared to studies done in Zimbabwe (AHR = 0.74), Kenya (AHR = 0.232), and Adama (AHR = 0.42),. 5 , 12 , 22 , 23 Patients with advanced WHO clinical stages III or IV also underwent more attrition from the treatment as compared to those in stage I. Early HIV diagnosis and initiation of treatment could increase survival rates; this might be due to the “Test and Treat” approach.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these previous studies have not reported TB treatment outcomes disaggregated by HIV status. It is likely the TB/HIV prevalence could also have changed over time because of the vast investment in controlling and preventing HIV or the increased access to ART by PLHIV [ 15 , 16 ]. Over the years, policy of HIV testing in Kenya has changed from self-initiated voluntary counselling & testing (VCT) to provider-initiated testing & counselling (PITC) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%